The Effect of Green Supply Chain Management Practices on the Sustainable Performance of the Textile Industry - Supamit Srisawat; Nongsom Srisawat (International Journal of Supply Chain Management, 2020)
The aim of the current study is to examine the effect of green supply chain management practices (GSCMP) on the sustainable performance (SP) of the textile industry of Indonesia. For this purpose, data was collected from the supply chain mangers of the textile industry through the questionnaire by using a convenient sampling technique. The Structural Equation Modeling (SEM) has shown that there is positive and significant relationship between the green manufacturing (GM) and SP. In the same vein, it is also found that green design (GD), green distribution (GD), eco-design (ED) and green manufacturing (GM) also have a positive and significant relationship with the SP in the textile industry of Indonesia. These findings indicate that textile industry in Indonesia has a greater importance on the GSCMP to increase the SP. Therefore, it could be explained that GSCMP are considered to be an important predictor to enhance the SP. The findings of the current study could contribute a body of literature in the form of empirical findings which could become a new area of research in future. The research limitations and future directions are also discussed at the end of the study.